Analysis of Bank Soundness Level Using RGEC Method in Banking Companies Listed on the Indonesia Stock Exchange in 2013-2017 - Rizki Robbi Izati; Sriyono Sriyono (Indonesian Journal of Law and Economics Review, 2022)
The purpose of this study was to determine the Bank's Health at PT. Bank BCA Tbk, PT. Bank BRI Agro Tbk and PT. Bank Danamon Tbk in terms of aspects of RGEC for the period 2013-2017. This research is a qualitative method with quantitative descriptive approach. The results of this study indicate that PT. Bank BCA Tbk, PT. Bank BRI Agro Tbk and PT. Bank Danamon Tbk from 2013 to 2017 as measured using risk profile methods, good corporate governance, earnings, capital (RGEC) is a healthy company. On the factor of Good Corporate Governance of PT. Bank BCA Tbk, PT. Bank BRI Agro Tbk and PT. Bank Danamon Tbk has implemented GCG principles in accordance with Bank Indonesia regulations. In the Earning factor which is considered a very healthy predicate. On the Capital factor assessed by the CAR ratio, it shows that PT. Bank BCA Tbk, PT. Bank BRI Agro Tbk and PT. Bank Danamon Tbk is very healthy.